THE DEVELOPMENT OF AUDIO-VISUAL STUDENT PORTFOLIOS (LKS) CONTEXTUAL TEACHING AND LEARNING-BASED (CTL) ON SOUND CHAPTER OF SCIENCE SUBJECT FOR DEAF STUDENTS - Susialita, T. (Jurnal Pendidikan IPA Indonesia, 2016)
The results of observation from several SLBs (Special School) showed that there was no LKS that accomodated Audio-Visual. So far, the LKS only available in the form of a handout that could be visualized, so that in science subject, the deaf students had difficulty in understanding sound chapter. In order to help deaf students understood sound chapter, the writer developed Audio-Visual LKS. The general purpose of this study was to develop the Audio-Visual LKS CTL-based on sound chapter of science subject for deaf srudents. The special purposes were (a) to produce Audio-Visual LKS CTL-based, (b) to describe the feasibility ofÂ  the product of Audio-Visual LKS CTL-based from the expertsâ valuations as well as the users with the rating instruments available, and (c) the effectiveness of Audio-Visual LKS CTL-based application to the understanding of sound chapter for deaf students at Grade IV. The development procedure used 4-D model which consists of stages of define, design, develop, and disseminate. This study perfomed limited test to five deaf students, and extensive test to 33 deaf students from several SLBs in Surabaya and Yogyakarta. The product resulted from this development was the Audio-Visual LKS CTL-based on sound chapter of science subject with the results of the feasibility from matter experts, media experts, and users that could be categorized as good/proper. The result of effectiveness analysis from all subjects obtained t count (7.510) > t table (1.694). Thus, it can be concluded that there is an effectiveness of application of Audio-Visual LKS CTL-based to the level of sound chapter understanding on science subject for deaf students at Grade IV.